Impulse response matching estimators for DSGE models - Pablo Guerron-Quintana; Atsushi Inoue; Lutz Kilian (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
One of the leading methods of estimating the structural parameters of DSGE mod- els is the VAR-based impulse response matching estimator. The existing asympotic theory for this estimator does not cover situations in which the number of impulse response parameters exceeds the number of VAR model parameters. Situations in which this order condition is violated arise routinely in applied work. We establish the consistency of the impulse response matching estimator in this situation, we derive its asymptotic distribution, and we show how this distribution can be approximated by bootstrap methods. Our methods of inference remain asymptotically valid when the order condition is satisfied, regardless of whether the usual rank condition for the application of the delta method holds. Our analysis sheds new light on the choice of the weighting matrix and covers both weakly and strongly identified DSGE model parameters. We also show that under our assumptions special care is needed to ensure the asymptotic validity of Bayesian methods of inference. A simulation study suggests that the frequentist and Bayesian point and interval estimators we propose are reasonably accurate in finite samples. We also show that using these methods may affect the substantive conclusions in empirical work.
urn:nbn:de:hebis:30:3-360551
Keywords: C32; C52; E30; E50; 330; structural estimation; DSGE; VAR; impulse response; nonstandard asymptotics; bootstrap; weak identification; robust inference